Comparison Between Primary and Secondary Pediatric Mucoepidermoid Carcinoma of the Head and Neck - Hao, Li; Shi, Caixiao; Xu, Ying (Frontiers in Pediatrics, 2020)
Objectives: Secondary mucoepidermoid carcinoma (MEC) of the head and neck is occasionally observed in childhood cancer survivors. The goal of this research was to compare the demographic and pathologic characteristics as well as survival between primary and secondary MEC in children and adolescent patients. Methods: Pediatric patients (younger than 19 years old) with surgically treated MEC of the head and neck were retrospectively enrolled at the Affiliated Children’s Hospital of Zhengzhou University and divided into two groups based on their cancer history. Demographic, pathologic, and survival characteristics between the two groups were compared. The main study interests were recurrence-free survival (RFS), overall survival (OS), and disease-specific survival (DSS). Results: The primary and secondary groups consisted of 63 and 15 patients, respectively. The two groups had similar distributions in terms of age, sex, tumor stage, neck lymph node stage, perineural invasion, lymphovascular invasion, p53, Bcl-2, proliferating cell nuclear antigen, carcinoembryonic antigen, and Ki-67 index. The 10-year RFS rates for the primary group and secondary group were 80% and 71%, respectively, and this difference was not significant (p=0.464). The 10-year DSS rates for the primary group and secondary group were 83% and 82%, respectively, and this difference was also not significant (p=0.649). The 10-year OS rates for the primary group and secondary group were 74% and 51%, respectively; this difference was significant (p=0.023). Further Cox model analysis confirmed the independence of a previous cancer history (p=0.043) in decreasing OS. Conclusions: Pediatric patients with secondary MEC exhibit similar demographic, pathologic, and molecular characteristics as primary patients but worse overall survival. These findings indicate that special disease management approaches might be needed for secondary patients.